Lithic Technological Organization at the Aztalan Site (47-je-0001) - (:unkn) unknown (My University, 2019)
Chipped stone artifacts represent just one aspect of a complex framework of behavioral adaptations to social and environmental forces, each requiring significant investments of both time and energy. This project consists of a complete lithic analysis of all chipped stone materials recovered by University of Wisconsin-Milwaukee field schools during 1984, 2011, and 2013 from the Aztalan site (47JE01), located in Southeastern Wisconsin. This assemblage includes 1,202 pieces of lithic debitage and 200 chipped stone tools. Through employing individual flake analysis of all debitage, this thesis has produced a large database of information that can provide valuable insight into the technological choices made by the people who lived at Aztalan. While Aztalan is a multi-component site, radiocarbon dating has placed the major prehistoric occupation of the Aztalan site between A.D. 1000-1200 (Richards and Jeske 2002) therefore, this thesis focuses on the overlapping Late Woodland and Middle-Mississippian components. The major goal of this thesis is to characterize the chipped stone artifacts from Aztalan through an assemblage-based approach, with the intention of answering questions relating to the lithic economy at the site. The UWM lithic assemblage suggests that lithic technological organization at Aztalan changed over time. Statistical analysis of the data from this project shows that with increased Middle Mississippian interaction came increased access to non-local raw materials. Not only was there an increase in access to non-local raw materials, but raw materials were also heat treated significantly less over time. Additionally, the results of this project suggest that the Late Woodland occupation at Aztalan may have already had access to a wider variety of raw materials than other Late Woodland groups in southeastern Wisconsin.